EFFECTIVENESS OF DIFFERENT DETERGENT SOLUTIONS AS LARVISIDE FOR AEDESAEGYPTI LARVAE - Sudarmaja, I Made; Swastika, I Kadek (BALI MEDICAL JOURNAL; Vol 4 No 1 (2015), 2015)
Background: Dengue hemorrhagic fever the spread of which is mediated by Aedesaegypti mosquito that becomes a health problem in Indonesia every year. Some natural and chemical substances had been experimented to combat Aedesaegypti, one of them is detergent solution. This study aims to investigate the effect of several concentrations of detergent to kill Aedesaegypti larvae, and to find out the lethal concentration (LC)50, LC90, and LC95. Method: Randomized posttest only control group design was applied to observe the percentage of Aedesaegypti larvae instar III-IV killed when they contacted to various detergent concentrations within 24 hour of observation. Results: This study result showed that detergent with the concentration of 0.12 g/l; 0.14 g/l; 0.16 g/l; 0.18 g/l; 0.20 g/l; 0.22 g/l and 0.24 g/l respectively showed the killing of Aedesaegypti larvae 37.6%, 42.4%, 74.4%, 85.6%, 89.6%, 95.2% and 100%, respectively. Probit analysis showed that LC50 = 0.14 gram/liter, LC90 = 0.20 g/l and LC95=0.22 g/l.
Keywords: Aedesaegypti, detergent, solution